2020
DOI: 10.3390/jcm9020419
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Underascertainment of Novel Coronavirus (2019-nCoV) Infection: Estimation Using Japanese Passengers Data on Evacuation Flights

Abstract: From 29 to 31 January 2020, a total of 565 Japanese citizens were evacuated from Wuhan, China on three chartered flights. All passengers were screened upon arrival in Japan for symptoms consistent with novel coronavirus (2019-nCoV) infection and tested for presence of the virus. Assuming that the mean detection window of the virus can be informed by the mean serial interval (estimated at 7.5 days), the ascertainment rate of infection was estimated at 9.2% (95% confidence interval: 5.0, 20.0). This indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
256
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 288 publications
(273 citation statements)
references
References 5 publications
14
256
1
2
Order By: Relevance
“…Our results showed that there is still a need for more comprehensive clinical studies, including short and long -term followup cohort assessments. More studies from outside China, where there are more than 100 patients diagnosed with COVID-19, as is the case of South Korea, Italy, and Japan [59,60], will contribute to the growing volume of data, in addition to the growing number of studies appearing from China. Even more, the situation with the cruise ship Diamond Princess, docked in Yokohama, Japan, with 3,711 passengers, approximately 20% of the infected, with 7 deaths, is also a valuable chance to better characterize COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that there is still a need for more comprehensive clinical studies, including short and long -term followup cohort assessments. More studies from outside China, where there are more than 100 patients diagnosed with COVID-19, as is the case of South Korea, Italy, and Japan [59,60], will contribute to the growing volume of data, in addition to the growing number of studies appearing from China. Even more, the situation with the cruise ship Diamond Princess, docked in Yokohama, Japan, with 3,711 passengers, approximately 20% of the infected, with 7 deaths, is also a valuable chance to better characterize COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…To take this effect into account, we assume 10% of the population are 'protected'. Recent studies showed the serial interval of COVID-19 could be as short as 5 days (Nishiura et al, 2020a), and the median incubation period could be as short as 4 days . These characteristics imply short latent period and infectious period.…”
Section: A Conceptual Modelmentioning
confidence: 99%
“…once any symptoms have manifested). The true fraction of subclinical COVID-19 cases remains unknown, but anecdotally, many lab-confirmed COVID-19 cases have not shown detectable symptoms on diagnosis (Hoehl et al, 2020;Nishiura et al, 2020;. About 80% of clinically attended cases have been mild (The Novel Coronavirus Pneumonia Emergency Response Epidemiology Team, 2020), and clinically attended cases have been conspicuously rare in children and teens The Novel Coronavirus Pneumonia Emergency Response Epidemiology Team, 2020;Huang et al, 2020;, raising the possibility that subclinical cases may be common.…”
Section: Introductionmentioning
confidence: 99%